Кровососущие мокрецы (Diptera, Ceratopogonidae и Leptoconopidae) Крыма - Шевченко, А.К. (Вестник зоологии, 1974)
The data on the Crimean fauna of biting midges are presented for different landscape-climatic zones and regions.. In all 40 species of biting midges from the Culicoides genus and one species from the Leptoconops genus were found in the Crimea. Some data on ecology (biotopes of development in different zones, periods of activity, etc.) are also given.